ANALYSIS OF THE IMPLEMENTATION OF SFAS NO. 55 ON THE ALLOWANCE FOR IMPAIRMENT LOSSES AT PT. BANK SULUT MANADO - Hilimi, Kurniawati; Karamoy, Herman (Universitas Sam Ratulangi, 2015)
The Financial Accounting Standards Board (FASB) has endorsed the relevant accounting standards related to the disclosure and presentation from January 1, 2012. Therefore, the rules for financial instruments are in IAS 55 (revised 2011) Financial Instruments: Recognition and Measurement. Reserve impairment losses is the amount derived from the carrying value to be valued at the recoverable amount of the asset. The purpose of this study to determine the extent and how the application of SFAS (Revised 2011) on Allowance for Impairment Losses is at PT. Bank Sulut Manado. The method is descriptive. The results shows the application of SFAS 55 (Revised 2011) on Allowance for Impairment Losses by PT. Bank Sulut Manado is in accordance with the applicable standards that SFAS 55 (Revised 2011). In the process of the recognition and measurement of loss reserves, in value decrease of PT. Bank Sulut Manado are in accordance with SFAS 55 (Revised 2011) and has been implemented well. it is expected in the future to be implemented consistently in order to produce accurate financial statements, and transparency to the operating results of the company. In recording accounts receivable, bank management should establish policies against the allowance of doubtful accounts for the company to prevent the occurrence of bad debts. Keywords: recognition and measurement, allowance for impairment losses